1976
DOI: 10.1017/s0022029900015685
|View full text |Cite
|
Sign up to set email alerts
|

αs0-Casein: its preparation and characterization

Abstract: It has been reported previously (Annan & Manson, 1969) that chromatography of the a s -casein complex of bovine milk on columns of sulphoethyl Sephadex C-50 resulted in fractionation of the complex into a main component, asj-casein and a number of minor components one of which was designated Os 0 -casein. The present communication describes the preparation of Os 0 -casein from unfractionated casein in an amount and state of purity which render possible its further characterization. EXPERIMENTAL Acid-precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Such a difference in composition between the two proteins is fully consistent with their behaviour when subjected to electrophoresis in starch/urea gels at pH 9.2 and 2.0. It was found that at pH 9.2 the aSo preparation migrated just ahead of aS1 casein B and at pH 2.0 it had a very slightly lower mobility than this protein, thus confirming earlier findings [2]. …”
Section: Conversion Of Phosphoseryl Residues To P-methylaminoalanyl Rsupporting
confidence: 88%
See 4 more Smart Citations
“…Such a difference in composition between the two proteins is fully consistent with their behaviour when subjected to electrophoresis in starch/urea gels at pH 9.2 and 2.0. It was found that at pH 9.2 the aSo preparation migrated just ahead of aS1 casein B and at pH 2.0 it had a very slightly lower mobility than this protein, thus confirming earlier findings [2]. …”
Section: Conversion Of Phosphoseryl Residues To P-methylaminoalanyl Rsupporting
confidence: 88%
“…The amino acid composition and phosphate content of M,O casein were determined on samples of the protein which had been prepared using the procedure described in the Methods section with the addition of a second cycle of the chromatographic purification. The results, which are set out in Table 1, indicate clearly that the amino acid composition of aSo casein did not differ, within experimental error, from that of a,l casein B and fail to support the earlier suggestion [2] that the two proteins differed from each other only by substitution of one histidyl by one aspartyl residue. In addition the aso casein preparations contained the equivalent of 8.7 mol phosphate/mol protein which, although close to the required value of 8.0 for aS1 casein, was nevertheless sufficiently removed from it to suggest that as0 casein contained 9 phosphate residues/mol compared with the 8 of c(,l casein.…”
Section: Conversion Of Phosphoseryl Residues To P-methylaminoalanyl Rmentioning
confidence: 62%
See 3 more Smart Citations